Increasing the rate of hydrogen oxidation without increasing the overpotential: a bio-inspired iron molecular electrocatalyst with an outer coordination sphere proton relay1. Issue 5 (20th May 2015) - Darmon, Jonathan M.; Kumar, Neeraj; Hulley, Elliott B.; Weiss, Charles J.; Raugei, Simone; Bullock, R. Morris; Helm, Monte L.
<x xml:space="preserve">Abstract</x> H2 oxidation by a molecular electrocatalyst is dramatically improved by controlling proton movement from iron to the outer coordination sphere.